Nucleophilic fluorination facilitated by a CsF–CaF2 packed bed reactor in continuous flow. Issue 7 (9th January 2018) - Johansen, M. B.; Lindhardt, A. T.
Abstract : A simple to prepare, dry and handle packed bed reactor carrying CsF on CaF2, towards nucleophilic fluorinations in continuous flow, is reported. Abstract : A simple to prepare, dry and handle packed bed reactor carrying CsF on CaF2, towards nucleophilic fluorinations in continuous flow, is reported. The reactor also proved adaptable for silyl-ether deprotection and trifluoromethylations with Ruppert's reagent. The study includes reactor stability and scale-up investigations.